Lateral Extra-Articular Tenodesis Reduces ACL Graft Force Under Multiplanar Torques Simulationg Pivot Shit. Issue 7 (31st July 2020) - Marom, Niv; Ouanezar, Herve; jahandar, hamidreza; Zayyad, Zaid; Fraychineaud, Thomas; Hurwit, Daniel; Imhauser, Carl; Wickiewicz, Thomas; Pearle, Andrew; Nawabi, Danyal
Objectives: Utilization of lateral extra-articular tenodesis (LET) in conjunction with anterior cruciate ligament reconstruction (ACLR) has increased in recent years, however, the biomechanical impact of LET, when performed with contemporary techniques, on both load sharing between the ACL graft and the LET and on knee kinematics is not completely clear. The purpose of this study was to quantify the effect of LET performed with ACLR, in the presence of a compromised anterolateral tissues, on (1) forces carried by the ACL graft and the LET and (2) knee kinematics, during simulated pivot shift. Methods: manipulator equipped with a six-axis force-torque sensor. The robot applied multiplanar torques simulating two types of pivot shift (PS) subluxing the lateral compartment at 15° and 30° of knee flexion. The following loading combinations were applied: (PS1) 8 Nm of valgus and 4 Nm of internal rotation torques; (PS2) 100 N compression force, 8 Nm valgus torque, 2 Nm internal rotation torque, and 30 N anterior force. Anteroposterior (AP) translation in the lateral compartment of the knee was recorded in the following states: ACL intact, sectioned, reconstructed and, finally, after sectioning the anterolateral ligament (ALL) and kaplan fibers and performing a LET. ACLR was performed utilizing a bone-patellar tendon-bone autograft, via medial parapatellar arthrotomy. LET was performed using a modified lemaire technique with a metal staple femoral fixation at 60° of flexion in neutral rotation. Resultant forces carried by the ACL graft and LET at the peak applied load in all tested conditions were determined utilizing the principle of superposition and serial sectioning. Results: Under both simulated pivot shift types and at both flexion angles the ACL force decreased with the addition of a LET, with the least force reduction of 39% for PS2 at 15° (p=0.01) and the most force reduction of 80% for PS1 at 30° (p<0.001). While decreasing ACL force, the LET carried at least 43% of the force carried by the ACL graft when tested without LET for PS2 at 15° and 91% of the force carried by the ACL graft at most, for PS1 at 30° (Table 1). For both combinations of multiplananr torques and at both flexion angles, the anterior tibial translation in the lateral compartment decreased for the ACLR+LET knee compared to the intact knee (5.3mm and 7.6mm decrease, for PS1 15° and 30° respectively, p<0.001; 4.4mm p=0.005 and 7.6mm p<0.001, for PS2 15° and 30°, respectively). (Figure 2). Conclusion: During a simulated pivot shift, LET shields the ACL graft from loading. This effect was greatest at 30° of flexion with an 80% drop in ACL graft force. While some shielding of load from the ACL graft can be beneficial, a more significant reduction in the load of the ACL graft may potentially be detrimental to the graft remodeling, maturation and function. The optimal load sharing pattern for improved clinical outcomes is not well understood and merit further investigation. In addition, LET also decreases anterior tibial translation in the lateral compartment to less than that of the intact knee, which represents overconstraint of the lateral compartment. These findings may support the purported "protective" effect of LET on the ACL graft and its important role in stabilizing the lateral compartment in the setting of combined ACL and anterolateral structures deficiency. The influence of overconstraint of the lateral compartment with LET warrants further biomechanical and clinical evaluation. Table 1. Mean loads carried by the ACL graft before and after the addition of a LET and loads carried by the LET, under both simulated pivot shift types at 15 ° and 30° of flexion Mean ACL Graft Loads (n=7) Mean LET Loads (n=7) Without LET With LET Difference % Drop* LET Load Relative Load** PS1 15° 58±13 N 20±23 N 29±18 N 49% 31±15 N 53% PS1 30° 54±13 N 11±7 N 44±12 N 80% 49±17 N 91% PS2 15° 68±15 N 41±20 N 26±19 N 39% 29±17 N 43% PS2 30° 71±15 N 21±20 N 50±14 N 70% 49±14 N 70% PS1=8 Nm of valgus and 4 Nm of internal rotation torques PS2=100 N compression, 8 Nm valgus, 2 Nm internal rotation, and 30 N anterior force *the percent of ACL graft force drop **The percent of load carried by LET relative to the load carried by ACL graft without LET Figure 1. Figure 2.